Pengaruh Metode Pembelajaran Picture untuk Meningkatkan Keaktifan Belajar Siswa di SD Negeri 0507 Pasar Latong - Irma Sari Daulay; Ahmad Paruntungan Daulay; Eka Putri Pulungan; Nedi Fahmi Tanjung; Nurul Pratama Hasibuan; Nur Halimah Siregar; Rahma Dhani Lubis (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to determine the effect of the Picture Learning Method on increasing student learning activeness in thematic learning class III SD Negeri 0507 Pasar Latong. The research method used was an experiment with a one-group pre-test and post-test design. The research sample amounted to 33 students selected through total sampling. Data collection techniques using observation, documentation, and tests in the form of pretests and posttests. The results showed a significant increase in student learning activeness after the Picture method was applied. The average pretest score of 63.06 increased to 85.75 in the posttest. The simple regression test results show the coefficient of determination (R²) of 0.342, which means that the Picture Method has an influence of 32.1% on student learning activities. Thus, it can be concluded that the Drawing Method is effective in increasing student learning activities, because it is able to create an interesting, innovative, and fun learning atmosphere.